Analysis of the influence of food types on human intelligence by correlation method - Nurhayati, Ai; Purnawan, Benny; Jatnika, Rohman Agus; Widiastuti, Meina; Mardaweni, Riri (Universitas Insan Cendekia Mandiri, 2025)
Every human being certainly needs nutritious food intake to support physical and mental strength in order to do all his daily activities. There are some human activities that require strong thinking power. Strong thinking skills can be obtained from adequate nutritional intake. The problem is that people do not know the great influence of food types on human intelligence. Therefore there needs to be research that calculates the magnitude of the influence of food types on intelligence. This research is important to do so that consumers can be good at choosing types of food that can increase human intelligence. The purpose of this study is to measure the magnitude of the influence of food types on the level of human intelligence. This research method uses the correlation analysis method. The results of this study indicate that protein food represented by fish has a positive influence on the level of human intelligence. The correlation value obtained from the calculation results is 0.796. The correlation value between 0.7 - 0.9 is included in the category of high linear relations. Therefore, there is a strong relationship between the number of fish consumed to intelligence. Fish is a type of food that contains albumin which is very important for the human intelligence system. Thus it can be concluded that the type of fish food has a strong influence on the level of human intelligence.